Imidazole propionate is increased in diabetes and associated with dietary patterns and altered microbial ecology - Antonio Molinaro (Nature Portfolio, 2020)
Gut microbial metabolism of nutrients contributes to metabolic diseases, and the histidine metabolite imidazole propionate (ImP) is produced by type 2 diabetes (T2D) associated microbiome. Here the authors report that circulating ImP levels are increased in subjects with prediabetes or T2D in three European populations, and this increase associates with altered gut microbiota rather than dietary histidine.